Effect of the Addition of Ca-PUFA Complexes to Complete Rations on Fermentability and Digestibility - Mutaqin, Bambang Kholiq; Tasripin, Didin S.; Adriani, Lovita; Tanuwiria, U. Hidayat (Pakistan Journal of Nutrition, 2019)
Background and Objective: The purpose of this study was to assess the sources of polyunsaturated fatty acids (PUFAs) in supplemental feed for dairy cows. Samples obtained from three types of vegetable oils (soybean oil, corn oil and peanut oil) were selected to provide essential fatty acids to dairy cows. Materials and Methods: The approach of this study was to compare three types of vegetable oils added to rations to make Ca-PUFA complexes given to dairy cows. The parameters measured were fermentability and digestibility. The completely randomized design was used with six treatments and four replications. The treatments were: R1 = Ration +3% Corn Oil, R2 = Basal Ration + 3% Peanut Oil, R3 = Basal Ration +3% Soybean Oil, R4 = Basal Ration +3% Ca-Corn Oil Complex, R5 = Basal Ration +3% Ca-Peanut Oil Complex and R6 = Basal Ration +3% Ca-Soybean Oil Complex. Results: This study indicated that the production of NH3 for the treatments ranged from 14.64±0.81 to 18.24±1.52 mM. The average volatile fatty acid (VFA) production ranged from 82.15±0.13 to 144.59±0.49 mM. The analysis of variance showed that the supplementation of Ca-oil complexes in complete rations increased VFA production values (p<0.05). Fatty acid compounding by calcium minerals improved digestibility compared to whole oil (p<0.05). Soybean oil compounded by calcium showed the highest fermentability and digestibility values among the three types of oils tested (corn oil, peanut oil and soybean oil). However, the results showed that peanut oil was comparable to soybean oil when considering economic factors. Conclusion: The use of peanut oil in the manufacturing of Ca-oil complexes can compete with soybean oil in terms of effectiveness.